Socio – Economic Factors Affecting Foreign Direct Investment in Pakistan - Ali, Sher (CITY UNIVERSITY RESEARCH JOURNAL, 2019)
Most of the developing countries facing the problem of capital shortage, one of the important reasons of it is low productivity or growth. These nations are intense need of capital inflow to reduce the mismatch is capital flow. FDI is one of the sources to over it or reduce it. Pakistan is one of the developing countries having lake of capital. Therefore, this aimed to investigate Socio-economic factors affecting FDI inflows to Pakistan. For this purpose, annual time series data is put into ARDL estimation technique. Stationarity tests are also used to know about the order of Stationarity. The results of estimation technique show that the cheap labors force significantly affect the inflow of FDI. Political instability and growth of GDP have also positive association with FDI inflow. Other important variables which are put into investigation and founded significant are related to nature of government and role of and quality of institutions. This study suggests on the bases of the findings that policy makers may give proper attention towards the quality of labor force which to be improved with education and skill. Institutional role and quality should be improved to attract more FDI to reduce or overcome capital shortage.